Synthesis, Experimental and Theoretical Studies by DFT on Molecular, Electronic, IR, NMR Analysis of 3-[(4-Methylbenzylidene)amino]phenol - Anbuselvi, S.; Jayamani, V.; Mathammal, R.; Sangeetha, R. (Asian Journal of Chemistry, 2012)
Synthesis and structural characterization by physical constants, IR, NMR and UV study of 3-[(4-methylbenzylidene)amino]phenol (4MBAP) was carried out. In order to present a full description, DFT calculations were carried out using B3LYP/6-31G(d,p) to obtain geometry, vibrational frequency and NMR data. The theoretical electronic spectra have been calculated by using CIS method. NBO analysis of 3-[(4-methylbenzylidene)amino]phenol was carried out. The observed and theoretical IR data of 3-[(4-methylbenzylidene)amino]phenol are compared. The FT-IR spectrum of the title compound was recorded in solid phase.